Effects of Stability Ball Training on Flexibility in Adolescents: A School-Based Intervention Study - Risky Amelia; Mita Erliana; M. Mulhim; Recky Ahmad Haffyandi (Jurnal Master Penjas & Olahraga, 2026)
This study aims to determine the effect of gym ball training on improving the bridge ability of students at SMPN 3 Gambut. This study employed a quantitative approach with a pre-experimental method using a one-group pretest and posttest design. The study sample consisted of 24 eighth-grade A students selected using purposive sampling. Data were collected through bridge ability tests administered before and after the treatment. The data were then analyzed using descriptive statistics, the Shapiro-Wilk normality test, and the Wilcoxon Signed-Rank Test. The results showed that the mean pretest score of 49.79 increased to 66.88 on the posttest, representing an increase of 17.09 points. The Wilcoxon Signed-Rank Test showed a significance value of 0.000 < 0.05. Therefore, it can be concluded that gym ball training has a significant effect on improving the bridge ability of students at SMPN 3 Gambut.